Perbedaan Lamanya Rawat Inap Pasien Post Appendektomi Pada Appendiksitis Akut dan Appendiksitis Perforasi - Septi Auliza Refolinda; Mizar Eriantono; Ringgo Alfarisi; Joan Willy (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Appendicitis is one of the causes of mortality rates 0,2 – 0,8% in the world. In Indonesia itself, appendicitis occupies the fourth most patients who undergo hospitalization. The worse this type of appendicitis, the longer the patient should undergo hospitalization in the hospital's surgical treatment room. The duration of the patient post-surgery is varied depending on the type of appendicitis suffered. This study aims to describe the difference in the length of stay in post appendectomy patients between acute appendicitis and perforated appendicitis. The research is a comparative analytical research retrospective with a cross-sectional approach. In this study, the samples were recorded from medical records of appendicitis patients in 2016-2019, totaling 60 respondents of acute appendicitis and 60 respondents of perforation appendicitis. The sampling techniques in this study used a total sampling technique. Analysis of data is using univariate analysis and Independent bivariate tests. It is known that the average length of inpatient hospitalization is acute for 9 days. The shortest hospitalization is for 2 days, and the longest is 23 days. The respondent with an appendicitis perforation with an average length of stay is 34 days, the shortest time hospitalization is 4 days, and the longest is 90 days. The Mann-Whitney U test showed a significant difference (p = 0,000 / p<0,005) of hospitalization length in acute appendicitis and perforation appendicitis of an appendectomy patient.